Comparative Proteomic Analysis of Flag Leaves Reveals New Insight into Wheat Heat Adaptation - Lu, Yunze; Li, Ruiqiong; Wang, Ruochen; Wang, Xiaoming; Zheng, Weijun; Sun, Qixin; Tong, Shaoming; Dai, Shaojun; Xu, Shengbao (Frontiers in Plant Science, 2017)
Hexaploid wheat (Triticum aestivum L.) is an important food crop but it is vulnerable to heat. The heat-responsive proteome of wheat remains to be fully elucidated because of previous technical and genomic limitations, and this has hindered our understanding of the mechanisms of wheat heat adaptation and advances in improving thermotolerance. Here, flag leaves of wheat during grain filling stage were subjected to high daytime temperature stress, and 258 heat-responsive proteins (HRPs) were identified with iTRAQ analysis. Enrichment analysis revealed that chlorophyll synthesis, carbon fixation, protein turnover, and redox regulation were the most remarkable heat-responsive processes. The HRPs involved in chlorophyll synthesis and carbon fixation were significantly decreased, together with severe membrane damage, demonstrating the specific effects of heat on photosynthesis of wheat leaves. In addition, the decrease in chlorophyll content may result from the decrease in HRPs involved in chlorophyll precursor synthesis. Further analysis showed that the accumulated effect of heat stress played a critical role in photosynthesis reduction, suggested that improvement in heat tolerance of photosynthesis, and extending heat tolerant period would be major research targets. The significantly accumulation of GSTs and Trxs in response to heat suggested their important roles in redox regulation, and they could be the promising candidates for improving wheat thermotolerance. In summary, our results provide new insight into wheat heat adaption and provide new perspectives on thermotolerance improvement.